Carboxymethyl holocellulose as alternative carbohydrate-based binder for biomass briquette development - Dewantoro, Awaly Ilham; Fauzan, Muklis; Lubis, Muhammad Adly Rahandi; Nurliasari, Desy; Mardawati, Efri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The use of starch as a binder in biomass briquette production raises concerns regarding food security, prompting the need for alternative, non-food-based binders. This study aimed to develop carboxymethyl holocellulose (CMH) derived from oil palm empty fruit bunches (OPEFBs) as a sustainable and effective binder for biomass briquettes made from coconut shells and sawdust. The OPEFBs were converted into CMH through a carboxymethylation process, yielding a product with a carboxyl content of 12.81% and a degree of substitution (DS) of 0.40, indicating effective modification. The synthesized CMH was used as a binder at various concentrations, with citric acid (CA) employed as a crosslinking agent. The total carboxyl content significantly increased with higher CA concentrations, demonstrating improved functional properties. Briquettes produced using CMH exhibited favorable proximate characteristics, such as low moisture content, high fixed carbon, and enhanced calorific value, particularly for coconut shell-based briquettes. The findings suggest that CMH can serve as an alternative to starch, providing sustainable and environmentally friendly solutions for biomass briquette production. Future studies should focus on optimizing the synthesis process and exploring CMHs’ performance in diverse biomass formulations.